Topological phase transition and interface states in hybrid plasmonic-photonic systems. (31st May 2017) - Ge, Lixin; Liu, Liang; Xiao, Meng; Du, Guiqiang; Shi, Lei; Han, Dezhuan; Chan, C T; Zi, Jian
Abstract: The geometric phase and topological property for one-dimensional hybrid plasmonic-photonic crystals consisting of a simple lattice of graphene sheets are investigated systematically. For transverse magnetic waves, both plasmonic and photonic modes exist in the momentum space. The accidental degeneracy point of these two kinds of modes is identified to be a diabolic point accompanied with a topological phase transition. For a closed loop around this degeneracy point, the Berry phase is π as a consequence of the discontinuous jump of the geometric Zak phase. The wave impedance is calculated analytically for the semi-infinite system, and the corresponding topological interface states either start from or terminate at the degeneracy point. This type of localized interface state may find potential applications in manipulation of photon emission of quantum dots, optical sensing and enhancement of nonlinear effects, etc.